Public Knowledge of Physical Pollution of River Water in Tanjung Selamat Village, Deli Serdang - Nanda, Meutia; Sari, Kurnia Permata; Fadila, Rianda; Harahap, Rosida Sapriani; Siregar, Siti Romaito (PROMOTOR, 2025)
Physical water pollution has become a serious environmental problem, primarily caused by domestic and livestock waste being directly discharged into rivers. This type of pollution is characterized by changes in the physical properties of water, such as color, odor, taste, and turbidity. This study aims to describe the community’s knowledge regarding river water pollution in Tanjung Selamat Village, Deli Serdang Regency. The research method used is descriptive qualitative with data collection techniques including interviews, observation, and documentation. The research informants consisted of 5 people, including 1 head of the neighborhood, 2 residents living along the riverbanks, and 2 street vendors operating near the river in Tanjung Selamat Village. The results showed that the level of community knowledge regarding water pollution is still low, as indicated by the ongoing practice of disposing of domestic waste directly into the river, which has led to physical water pollution in the area. Therefore, it is necessary to conduct continuous outreach, environmental education, and counseling programs for the community, particularly those residing near the river. It is expected that by increasing public awareness and knowledge, efforts to maintain the cleanliness of rivers in Tanjung Selamat Village, Deli Serdang, can be realized.